Antistaphylococcal Activity of LBM415, a New Peptide Deformylase Inhibitor, Compared with Those of Other Agents - Credito, Kim (American Society for Microbiology, 2004)
The MICs of LBM415, a new peptide diformylase inhibitor, were ≤0.06 to 4.0 μg/ml for 258 isolates of Staphylococcus aureus and coagulase-negative staphylococci. LBM415 MICs were similar irrespective of whether the strains were methicillin susceptible or resistant. All strains were also susceptible to vancomycin, linezolid, ranbezolid, daptomycin, oritavancin, and quinupristin-dalfopristin. LBM415 at the MIC was bacteriostatic after 24 h.